PERBEDAAN RASM UTHMĀNI DAN KAIDAH IMLĀ` DALAM PENULISAN AL-QUR’AN SERTA IMPLIKASINYA TERHADAP PENAFSIRAN - Rofi'i, Muhammad Arwani; Nurin Alfiani; Zahrotus Tsaniyah Dhuhia Shofianah (STAI AL-ANWAR SARANG, 2024)
The writing of the Qur’anic manuscript has undergone significant stages since the time of the Prophet Muhammad (PBUH), culminating in its official codification during the caliphate of Uthman ibn ‘Affan, known as Rasm Uthmani. This codification became the standard for the transcription of Qur’anic manuscripts throughout the Islamic world. However, this writing system differs fundamentally from the modern Imla’ (orthographic) rules used in contemporary Arabic. This study aims to identify and analyze the differences between Rasm Uthmani and Imla’ conventions, as well as to explore their linguistic and interpretative implications for understanding the sacred text. The research adopts a qualitative approach using library research methods and content analysis of selected Qur’anic verses that exhibit distinctive orthographic features. The findings reveal that Rasm Uthmani is not merely a conventional script but carries profound and symbolic meanings that are not always accessible through standard Imla’ approaches. Certain spellings that appear inconsistent with modern phonetics in fact convey semantic signals that enrich exegetical interpretations. Therefore, understanding these differences is crucial in the context of Qur’anic interpretation, both classical and contemporary. This study recommends that tafsir scholars pay greater attention to rasm aspects as an integral component in comprehensively grasping the divine message.